A writing between Ríos - Toledo, Alejandro (Tropelías: Review of Literary Theory and Comparative Literature, 2021)
In some handwritten note, Octavio Paz defined Julián Ríos (Galicia, 1941) as a "plural" writer, which in principle was true in a very direct way since it was the Plural magazine —which was directed by the Mexican Nobel Prize winner in the early seventies of the twentieth century— the medium in which the initial fragments of the Larva series appeared, and it continued to be because of that complex breath of plurality in Ríos' now extensive work that encompasses almost a dozen titles between narrative and essay, with its permutations and intersections, plus the "painted novels", guided tours through the drawings and paintings of artists such as RB Kitaj or Antonio Saura.